Contact, conquest and colonization
1 online resource.
Keywords: "Contact, Conquest and Colonization brings together international historians and literary studies scholars in order to explore the force of practices of comparing in shaping empires and colonial relations at different points in time and around the globe. Whenever there was cultural contact in the context of European colonization and empire-building, historical records teem with comparisons between those cultures. This edited volume focuses on what historical agents actually do when they compare, rather than on comparison as an analytic method. Its contributors are thus interested in the 'doing of comparison', and explore the force of these practices of comparing in shaping empires and (post-)colonial relations between the sixteenth and twentieth centuries. This book will appeal to students and scholars of global history, as well as those interested in cultural history and the history of colonialism"--